SOLITARY JUVENILE RECTAL POLYP IN A TODDLER PRESENTING WITH PROLAPSE AND HEMATOCHEZIA: A CASE REPORT AND COMPREHENSIVE REVIEW OF DESMOID-TYPE FIBROMATOSIS - Hassita Wenda Mayrina; Harisma Widhanar (The International Journal of Medical Science and Health Research, 2025)
Introduction: Juvenile polyps are the most common cause of lower gastrointestinal bleeding in the pediatric population. These lesions are typically benign hamartomatous growths, and a solitary polyp is rarely associated with long-term morbidity. This report aims to present a classic case of a solitary juvenile polyp leading to significant clinical symptoms in a toddler. Additionally, it provides a comprehensive, state-of-the-art review of desmoid-type fibromatosis, a rare soft tissue neoplasm that, while unrelated to this case's final diagnosis, represents an important entity in the differential diagnosis of pediatric masses. Case Illustration: A 19-month-old male presented to the emergency department with a seven-day history of progressively worsening hematochezia and a one-day history of a prolapsed, irreducible rectal mass. The patient exhibited signs of weakness and anemia. Physical examination revealed a 3x2x2 cm, fresh red, pedunculated mass protruding from the anus. After initial stabilization, the patient underwent a transanal polypectomy. The post-operative course was complicated by significant hemorrhage on the second day, which was managed successfully with conservative measures, including tranexamic acid. Histopathological examination of the excised specimen confirmed the diagnosis of a benign hamartomatous juvenile polyp. Discussion: The diagnosis and management of the solitary juvenile polyp were consistent with established clinical practice. Simple polypectomy is curative, and further surveillance is generally not required in the absence of multiple polyps or a family history of polyposis syndromes. The main focus of this discussion is a detailed review of desmoid-type fibromatosis. This entity is defined as a locally aggressive, non-metastasizing fibroblastic neoplasm. Its pathogenesis is driven by dysregulation of the Wnt/β-catenin signaling pathway. A significant paradigm shift has occurred in its management, moving away from aggressive upfront surgery towards a more conservative approach centered on active surveillance, with systemic therapies like tyrosine kinase inhibitors and gamma-secretase inhibitors reserved for progressive or symptomatic disease. Conclusion: Solitary juvenile polyps are a common and highly treatable cause of rectal bleeding in children. This case highlights the typical presentation and a potential post-operative complication. The accompanying review of desmoid-type fibromatosis serves an important educational purpose, underscoring the evolving management strategies for rare soft tissue tumors, which prioritize balancing disease control with long-term quality of life.